Heterogeneity of primary and secondary peristalsis in systemic sclerosis: A new model of "scleroderma esophagus". Issue 7 (28th October 2021) - Carlson, Dustin A.; Prescott, Jacqueline E.; Germond, Emma; Brenner, Darren; Carns, Mary; Correia, Chase S.; Tetreault, Marie‐Pier; McMahan, Zsuzsanna H.; Hinchcliff, Monique; Kou, Wenjun; Kahrilas, Peter J.; Perlman, Harris R.; et al.
Abstract: Background: Although esophageal dysmotility is common in systemic sclerosis (SSc)/scleroderma, little is known regarding the pathophysiology of motor abnormalities driving reflux severity and dysphagia. This study aimed to assess primary and secondary peristalsis in SSc using a comprehensive esophageal motility assessment applying high‐resolution manometry (HRM) and functional luminal imaging probe (FLIP) Panometry. Methods: A total of 32 patients with scleroderma (28 female; ages 38–77; 20 limited SSc, 12 diffuse SSc) completed FLIP Panometry and HRM. Secondary peristalsis, i.e., contractile responses (CR), was classified on FLIP Panometry by pattern of contractility as normal (NCR), borderline (BCR), impaired/disordered (IDCR), or absent (ACR). Primary peristalsis on HRM was assessed according to the Chicago classification. Results: The manometric diagnoses were 56% ( n  = 18) absent contractility, 22% ( n  = 7) ineffective esophageal motility (IEM), and 22% ( n  = 7) normal motility. Secondary peristalsis (CRs) included 38% ( n  = 12) ACR, 38% ( n  = 12) IDCR, 19% ( n =  6) BCR, and 15% ( n =  5) NCR. The median (IQR) esophagogastric junction (EGJ) distensibility index (DI) was 5.8 mm 2 /mmHg (4.8–10.1) mm 2 /mmHg; EGJ‐DI was >8.0 mm 2 /mmHg in 31%, and >2.0 mm 2 /mmHg in 100% of patients. Among 18 patients with absent contractility on HRM, 11 had ACR, 5 had IDCR, and 2 had BCR. Among 7 patients with IEM, 1 had ACR, 5 had IDCR, and 1 NCR. All of the patients with normal peristalsis had NCR or BCR. Conclusions: This was the first study assessing combined HRM and FLIP Panometry in a cohort of SSc patients, which demonstrated heterogeneity in primary and secondary peristalsis. This complementary approach facilitates characterizing esophageal function in SSc, although future study to examine clinical outcomes remains necessary. Abstract : A comprehensive motility assessment using high‐resolution manometry (HRM) and functional luminal imaging probe (FLIP) Panometry to assess primary and secondary peristalsis, respectively, may facilitate characterizing subtypes of esophageal function in systemic sclerosis.